2018
DOI: 10.1139/cjfr-2016-0537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phenological synchronization on caterpillar early-instar survival under a changing climate

Abstract: Early-instar caterpillars experience very high and often very variable mortality; if it is density dependent, it can be a key factor in outbreak dynamics. Plant physical and chemical defenses can be extremely effective against young caterpillars, even of specialists. Phenological asynchrony with host plants can lead to dispersal and mortality in the early instars and increased predation or poor nutrition in later instars. Predation on early-instar larvae (including cannibalism) can be extremely high, parasitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 83 publications
1
28
0
1
Order By: Relevance
“…This effect could be due to its later bud flush ensuring that SBW larvae have a food resource for longer in the season, which could maintain populations at higher levels for multiple years. Thus, fir trees re-flushing in subsequent years would be more vulnerable in the presence of spruce (Blais 1957;Despland 2017). In fir-spruce mixtures, the SBW seems to act as a biological filter to reduce fir abundance in favor of spruce (Kneeshaw and Bergeron 1998;Kneeshaw and others 2015).…”
Section: Balsam Fir Forests: the Importance Of Pre-disturbance Conditmentioning
confidence: 97%
“…This effect could be due to its later bud flush ensuring that SBW larvae have a food resource for longer in the season, which could maintain populations at higher levels for multiple years. Thus, fir trees re-flushing in subsequent years would be more vulnerable in the presence of spruce (Blais 1957;Despland 2017). In fir-spruce mixtures, the SBW seems to act as a biological filter to reduce fir abundance in favor of spruce (Kneeshaw and Bergeron 1998;Kneeshaw and others 2015).…”
Section: Balsam Fir Forests: the Importance Of Pre-disturbance Conditmentioning
confidence: 97%
“…Over the 2 years of our study, we observed phenological synchrony between adult monarch arrival (i.e., egg-laying) and bud burst/young expanding foliage of showy milkweed. Research on eastern monarchs has shown that phenological asynchrony with milkweed host plants can lead to high mortality of early instars and increased predation or poor nutrition in later instars (Zalucki et al, 2011), though how this mortality contributes to overall population dynamics remains unclear (Despland, 2017).…”
Section: Characteristics Of Monarch Breeding Habitatmentioning
confidence: 99%
“…In general, the leaf surface influences the ability of insect herbivores to establish a feeding site, especially in the early larval instars when mandibles are small (Despland, 2018) as newly emerged larvae must pierce the leaf cuticle to access the nutritious tissues underneath (Clissold, 2008). Tough leaves, or additional surface features such as waxes or trichomes, can increase the food processing time required by caterpillars to remove or circumvent these obstructions in order to access the nutritious leaf parenchyma (Voigt et al, 2007;Shelomi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the observation, survival was evaluated by leaving caterpillars for 24 h on the leaf on which they had been observed in mesh cages that exclude predators. Shortterm hatchling survival in the absence of predation provides an index of success in overcoming plant defenses and initiating feeding (Despland, 2018). The number of holes in the leaf (feeding initiation sites) was also recorded to test whether caterpillars on washed leaves were more likely to have initiated feeding independently rather than use a feeding edge created by a conspecific.…”
Section: Laboratory Experimentsmentioning
confidence: 99%